Gender differences in computer attitudes and skills - Tengku Faekah bt Tengku Ariffin, (penerbit ukm, 2005)
Studies on computer use in education have taken into account the gender factor since the 1980s. However, results regarding gender differences have not been consistent, especially from the aspect of attitudes towards computers. This study indentifies student’s attitudes toward computer technology and their skills in using computers. Information for this study has been gathered from a survey on 556 students in the district of Kubang Pasu, Kedah. Results show that generally, students have positive attitudes toward computers, but they have low skills in using computers. Female students have more confidence and positive attitudes toward the importance of computers. Male students however reported having better skills in handling computers. This article offered suggestions to strengthen the positive attitudes and expand the skills of using computers among students.